2011
DOI: 10.1002/asia.201000744
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Effects of para‐Substitution on the Melting Points of TAAILs

Abstract: Owing to numerous new applications, the interest in “task‐specific” ionic liquids increased significantly over the last decade. But, unfortunately, the imidazolium‐based ionic liquids (by far the most frequently used cations) have serious limitations when it comes to modifications of their properties. The new generation of ionic liquids, called tunable aryl–alkyl ionic liquids (TAAILs), replaces one of the two alkyl chains on the imidazolium ring with an aryl ring which allows a large degree of functionalizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…Molecular volumes of the cations were calculated using the COSMO model [8b] and are given in Ta ble 1. The volumes cover ar ange from 0.228 to 0.518 nm 3 ,a nd hence may be compared to common 1-n-alkyl-3-methyl imidazolium ions from [C 5 MIm] + (0.220 nm 3 )t o[ C 10 MIm] + (0.331 nm 3 )o rt oa mmonium cations from [N 2225 ] + (0.268 nm 3 )t o[ N 1888 ] + (0.604 nm 3 ). In the case of R 1 = 4-OMeo rM es, viscosities seem to decrease with increasing chain length, buto nly when combined with the borate anion.I fR 1 = 2-Me, viscosities reach aminimum at R 2 = Hex.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular volumes of the cations were calculated using the COSMO model [8b] and are given in Ta ble 1. The volumes cover ar ange from 0.228 to 0.518 nm 3 ,a nd hence may be compared to common 1-n-alkyl-3-methyl imidazolium ions from [C 5 MIm] + (0.220 nm 3 )t o[ C 10 MIm] + (0.331 nm 3 )o rt oa mmonium cations from [N 2225 ] + (0.268 nm 3 )t o[ N 1888 ] + (0.604 nm 3 ). In the case of R 1 = 4-OMeo rM es, viscosities seem to decrease with increasing chain length, buto nly when combined with the borate anion.I fR 1 = 2-Me, viscosities reach aminimum at R 2 = Hex.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
“…In the last few years a new generation of imidazolium‐based ionic liquids, called TAAILs (tunable alkyl aryl ionic liquids), has been developed, which can be distinguished from the standard ionic liquids by the (substituted) phenyl ring at the N‐1 nitrogen atom of the imidazolium heterocycle. Depending on the type, number, and position of substituent(s) at the phenyl ring (and the length of the alkyl chain at the N‐3 nitrogen atom of the imidazolium heterocycle), we can change the electronic properties of the resulting ionic liquids through additional mesomeric and steric effects, which can easily be seen from the melting points . By changing the core of the new ionic liquids from imidazolium to triazolium, it was demonstrated that not only the phenyl ring plays an important role …”
Section: Introductionmentioning
confidence: 99%
“…Interesting effects were found not only for imidazolium based, but also for triazolium based TAAILs . Also the type (electron‐donating or –withdrawing) and position of the substituents at the phenyl ring, the alkyl chain length and the anion lead to different properties. Currently different applications are under investigation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of a spherical halide counterion by a calamitic sulfonimide anion indeed led to a decrease of the melting points, the effect being larger for trifluorosulfonimides 2a and 3a as compared to methylsulfonimides 2b and 3b . It should be noted that Strassner has recently introduced a different concept to tune melting points in ionic liquids by electronic effects of the aryl substituent [4445]. However, the mesogenic sulfonimide resulted in the formation of a SmA mesophase only in the case of 3b , while ion pairs 2a , b and 3a did not show any liquid-crystalline properties.…”
Section: Resultsmentioning
confidence: 99%